Atrioventricular reciprocal rhythm and chronic reciprocating tachycardia in a newborn infant with concealed Wolff-Parkinson-White syndrome. Issue 7 (July 1977) - Sung, R J; Ferrer, P; Garcia, O L; Castellanos, A; Gelband, H
Abstract : A case of atrioventricular reciprocal rhythm and chronic reciprocating tachycardia in a newborn infant is presented. Electrophysiological studies suggest that these rhythm disturbances are related to the presence of a right-sided atrioventricular accessory pathway capable only of retrograde conduction (concealed Wolff-Parkinson-White syndrome). The technique of recording the sequence of atrial activation during the tachycardia is described and its clinical importance emphasised.